Hydrogeochemistry and Netpath Modeling of Groundwater in Taklimakan Desert, China - Fan, Jinglong; Xu, Xinwen; Lei, Jiaqiang; Li, Shengyu (Asian Journal of Chemistry, 2014)
The eco-environment is highly dependent on groundwater in arid areas, especially in desert. Because of the scarcity of surface water resources within the Taklimakan desert, a groundwater-fed water supply system was constructed by Shelter-forest ecological engineering and oilfield engineering in the hinterland of the desert. The groundwater’s TDS concentrations were relatively high in the north and lower in the south. A continuous evaporation and leached effects lead to the downstream ion concentration increased. Natural rock salt was dissolved always and the calcite was at precipitation state, resulting in a decrease of the HCO3– concentration. Due to the fewer amounts of orthoclase and the precipitation state of muscovite in chemical reaction, the potassium content was low in groundwater solution. The above processes may ultimately results in a groundwater of Cl-SO4-Na type that resulting in the formation of brine in the downstream.